PRACTICE OF FOREST AREA CLEARANCE IN KUBU DISTRICT, KARANGASEM, BALI - Monda, Ida Gemawati; Merta, I Made Merta; Sulistyawati, Sulistyawati Sulistyawati; Wiasti, Ni Made Wiasti (E-Journal of Cultural Studies; Vol 8 No 3 (2015): Volume 8, Number 3, August 2015, 2015)
The phenomenon of forest clearance is a holistic problem which has caused a forest not to function optimally. The first consequence of forest clearance is felt by the people living around the forest. It can lead to fire, landslide and the disappearance of water source. It can also cause the micro climate to decrease. The theories used in the present study are the theory of power discourse and knowledge proposed by Foucault, the theory of hegemony proposed by Antonio Gramci, and the theory of communication action, proposed by Habermas. It was found that; first, those who cleared the trees growing in the forest area away come from the surrounding villages. The culture of such a forest clearance had been done from generation to generation. The closer they lived to the forest area, the more cattle they raised. They raised more or less four cattle without being supported with how to prepare the food they need. Second, the government had made many attempts to overcome the forest clearance at the Kubu Forest Management Resort “ Resor Pengelolaan Hutan (RPH) Kubu” ; however, the attempts which it had made was not well communicated. Third, the view of the people involved in the forest area clearance was different from the government’s policy. Fourth, if related to Tulamben Village as a tourist destination, the areas within and outside the forest had the potentials which could be developed as the solution to the forest area clearance.
Keywords: forest area clearance, protected forest area, RPH production forest.